Design, synthesis and biological evaluation of mono- and bisquinoline methanamine derivatives as potential antiplasmodial agents. (15th April 2021) - Bokosi, Fostino R.B.; Beteck, Richard M.; Mbaba, Mziyanda; Mtshare, Thanduxolo E.; Laming, Dustin; Hoppe, Heinrich C.; Khanye, Setshaba D.
Graphical abstract: Highlights: A series of thirty-nine quinoline derivatives has been synthesised and characterised by common spectroscopic techniques. Most compounds displayed significant antiplasmodial activity with IC50 values from mid to sub-micromolar. Compounds 40 and 59 displayed strong binding mode to hemozoin crystal after computational docking. Abstract: Several classes of antimalarial drugs are currently available, although issues of toxicity and the emergence of drug resistant malaria parasites have reduced their overall therapeutic efficiency. Quinoline based antiplasmodial drugs have unequivocally been long-established and continue to inspire the design of new antimalarial agents. Herein, a series of mono- and bisquinoline methanamine derivatives were synthesised through sequential steps; Vilsmeier-Haack, reductive amination, and nucleophilic substitution, and obtained in low to excellent yields. The resulting compounds were investigated for in vitro antiplasmodial activity against the 3D7 chloroquine-sensitive strain of Plasmodium falciparum, and compounds 40 and 59 emerged as the most promising with IC50 values of 0.23 and 0.93 µM, respectively. The most promising compounds were also evaluated in silico by molecular docking protocols for binding affinity to the {0 0 1} fast-growing face of a hemozoin crystal model.